Esensi Khulu’ dalam Hadis Riwayat Ibnu Abbâs Perspektif Maqâshid Al-Syari’ah - Zikri Darussamin (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
As a mitsaqan ghaliza, the marriage bond is based on a strong commitment, guarded with sincerity and should not be neglected or separated easily. In principle, Islam allows divorce as a halal solution that Allah hates as well as an emergency exit to end an unhealthy marriage when all other efforts have failed. However, based on a hadith narrated by Ibn 'Abbas, it seems that divorce can be done easily through the khulu' route. This paper aims to analyze the hadith narrated by Ibn 'Abbas, about the wife of Tsabit bin Qais who requested khulu' from her husband with a ransom. This research uses the takhrîj method with the approach of textual interpretation, contextual and intertextual interpretation. By exploring the sanad and matn, this study concludes that the hadith belongs to the group of ahâd traditions, is authentic and can be used evidence (hujjah). In the perspective of maqâshid al-syârî'ah, the essence of khulu' in the Hadith of Ibn Abbas is a form of Islamic protection of women's rights as a vulnerable group in the household institution which contains the values of hifz aql (protection of the benefit of the intellect) and the values of hifz nafs (protection of the benefit of the soul).  As an emergency exit, khulu' is a balanced solution for women who face household chaos to avoid harm.